Assessment of the Influence of Dredge Spoil Dumping on the Seafloor Geological Integrity - Virtasalo, Joonas J.; Korpinen, Samuli; Kotilainen, Aarno T. (Frontiers in Marine Science, 2018)
The European Marine Strategy Framework Directive requires the development of suitable indicators for regular reporting on the environmental state and achievement of a good environmental status of EU’s marine waters by 2020. The development of indicators for determining seafloor integrity and its possible disturbance by human activities have so far largely ignored the geological properties of seafloor. This paper presents a study of Vuosaari and Uusikaupunki-D offshore dumping sites in Finland, the northern Baltic Sea. Full coverage multibeam bathymetry and relative backscatter data, and a number of sediment cores were collected over the sites. The areas covered by dumped dredge spoil stand out in the multibeam images because of their irregular surface and elevated backscatter. The short gravity cores were studied for lithology, and in 1-cm slices for 137Cs activity, organic content, and grain size distribution. The dumped material is represented in the cores by the gravelly mud lithofacies with massive texture and angular coarse particles. The dumped material is coarser, less sorted and has higher kurtosis compared to natural sediment due to the admixing of blasted rock during the dredging activities, and limited sorting during fall through the water column upon dumping. Dispersed dredge spoil, which was suspended in the water column during the dumping activities or reworked from the dumped material mounds and redistributed along the seafloor soon thereafter, was deposited over a wide area as a thin layer that is not necessarily readily identifiable by visual inspection in the cores. Cesium activity helped distinguish the dumped material from the 137Cs-enriched natural sediments deposited after the 1986 Chernobyl disaster. Considering that the dumped material at many of the coring sites in the Vuosaari dumping area is covered by natural sediment, it probably is largely stable. In contrast, dumped material at the shallower Uusikaupunki-D site has slumped down to an adjacent channel and is likely being redistributed by near-bottom currents. Based on the findings of the study, a protocol for the assessment of the geological integrity of seafloor, its anthropogenic change due to dumping, and its potential recovery is proposed, as required by the Marine Strategy Framework Directive.